What makes locked-down students happy: The sense of mattering and subjective well-being - Hao Wang; Kususanto Ditto Prihadi (International Journal of Evaluation and Research in Education (IJERE), 2022)
Subjective well-being (SWB) of university students who had to study off-campus due to the pandemic was investigated in this current study. Studies had reported that one of the most robust factors of SWB is the sense of mattering. While the sense of mattering is built upon social feedback, being locked down limited their source of social feedback to they can only develop their interpersonal mattering through their significant others whom they shared the dwelling place and their societal mattering through the ‘society’ they found in the social media. We purposively selected 82 participants to respond to our scales of mattering types and SWB. Among our inclusion criteria was to have a limited number of living partners (0-3) to make sure that their mattering was predominantly built from the social media feedback. The result of the multiple regression analysis suggested that despite their interpersonal mattering having a weaker contribution to their SWB, it was still a significant predictor of SWB when controlling for societal mattering. Thus, both types of mattering are still considered salient and robust predictors of SWB. Further limitations and suggestions are discussed.